Dampak Pemahaman Wajib Pajak Usaha Mikro, Kecil, dan Menengah terhadap Kepatuhan Perpajakan dengan Berlakunya Peraturan Pemerintah Nomor 55 Tahun 2022 - Budiarsa, Alika Aurazaviera (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the sectors that contribute the largest tax revenue in Indonesia. However, MSMEs experienced quite serious challenges during the COVID-19 pandemic. As an effort to revive MSMEs economy, in 2022, the government issued the latest regulations regarding the gross turnover limit for individual MSMEs which are not subject to income tax, so MSMEs can be helped in carrying out their business activities and have the awareness to comply with tax regulations. Based on this, it’s necessary to research the understanding and compliance MSMEs of Government Regulation Number 55 of 2022 to determine the understanding of MSMEs Taxpayers regarding tax compliance with the enactment of Government Regulation Number 55 of 2022 using a qualitative descriptive approach and collecting information using interview and questionnaire methods to six taxpayers located in the Special Region of Jakarta and the city of Bandung. The results show that MSME Taxpayers are aware of the latest changes regarding MSME income tax incentives, have a good understanding of their contents, and increase taxpayer compliance as demonstrated by the absence of sanctions imposed on Taxpayers. Even though MSME Taxpayers said that the provision of the latest incentives would attract the interest of MSME performer to report taxes, different results were obtained where the MSME performer were not interested in reporting taxes because their poor understanding of taxation. Therefore, it is hoped that the regulator can provide tax socialization which can be provided through MSME associations to reach a wider audience. Keywords: Government Regulation Number 23 of 2018, Government Regulation Number 55 of 2022, MSME Income Tax Incentives, Tax Compliance, Tax Understanding,